2009
DOI: 10.1152/ajpcell.00070.2009
|View full text |Cite
|
Sign up to set email alerts
|

The role of PGC-1α on mitochondrial function and apoptotic susceptibility in muscle

Abstract: Mitochondria are critical for cellular bioenergetics, and they mediate apoptosis within cells. We used whole body peroxisome proliferator-activated receptor-gamma coactivator-1alpha (PGC-1alpha) knockout (KO) animals to investigate its role on organelle function, apoptotic signaling, and cytochrome-c oxidase activity, an indicator of mitochondrial content, in muscle and other tissues (brain, liver, and pancreas). Lack of PGC-1alpha reduced mitochondrial content in all muscles (17-44%; P < 0.05) but had no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
119
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 41 publications
8
119
0
Order By: Relevance
“…Furthermore, prolonged mTORC1 inactivation in quiescent myotubes led to the upregulation of certain mitochondrial indicators, although this came at the expense of mitochondrial respiration, reminiscent of cells with mitochondrial disease. This defect could be recovered with the addition of CCA, further fortifying a role for contractile activity in ameliorating mitochondrial dysfunction in muscle (2,21). …”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, prolonged mTORC1 inactivation in quiescent myotubes led to the upregulation of certain mitochondrial indicators, although this came at the expense of mitochondrial respiration, reminiscent of cells with mitochondrial disease. This defect could be recovered with the addition of CCA, further fortifying a role for contractile activity in ameliorating mitochondrial dysfunction in muscle (2,21). …”
Section: Discussionmentioning
confidence: 98%
“…Reductions in PGC-1␣ are also seen in humans and mice fed a high-fat diet (16,52) and obese mice (16). PGC-1␣ knockout mice have reduced mitochondrial content in white and red muscles, altered mitochondrial function, and increased susceptibility to apoptosis (2). Further work is needed to determine whether PGC-1␣ expression is a critical regulatory event for wasting of glycolytic and oxidative skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PGC-1␣ can regulate mitochondrial biogenesis. PGC-1␣ loss impairs mitochondrial respiratory function and enhances mitochondrial oxidative stress and apoptotic susceptibility (2,25,40). Haemmerle et al (15) reported that the PGC-1␣ signaling pathway is a potential therapeutic target for the treatment of patients with neutral lipid storage disease.…”
Section: Discussionmentioning
confidence: 99%